Students’ Experiences in Building Confidence through Project-Based Learning in Video-Based Speaking Assessments - Rahmaniah, Sovia; Amelia, Rizky; Luthfiyanti, Lita (English Department of Faculty of Tarbiyah and Teacher Training, 2025)
Students may find speaking difficult when having nervousness, self-doubt, and a lack of confidence. Some previous research has found that video projects as an authentic assessment tool in project-based learning can enhance students’ confidence in talking. Then, this study explores the students’ experiences in building confidence through video-based assessments within a Project-Based Learning (PBL) framework. Using qualitative analysis of survey data, the research examines students’ experiences and challenges associated with this approach. The findings indicate that most students experienced increased speaking confidence due to repeated practice, self-evaluation, and exposure to real-world communication settings. However, challenges such as technical difficulties and anxiety about speaking on camera were also reported. Despite these obstacles, students found PBL with video projects engaging and effective in boosting their confidence. These results suggest that video-based assessments can be a valuable tool in PBL to support the development of students’ speaking confidence.